Synergistic effects of intermolecular copigmentation and high-pressure processing on stabilizing mangosteen pericarp anthocyanins - Ijod, Giroon; Mohamed Nawawi, Nur Izzati; Qoms, Mohammed S.; Rashedi Ismail Fitry, Mohammad; Abd Rahim, Muhamad Hafiz; Charalampopoulos, Dimitris; Sulaiman, Rabiha; Mohd Adzahan, Noranizan; Mohamad Azman, Ezzat (Elsevier, 2025)
The mangosteen pericarp contains unstable non-acylated ACNs, rendering it prone to degradation. Therefore, intermolecular copigmentation of semi-purified ACNs (SPA) with tartaric acid (SPA-TA), sinapic acid (SPA-SA), catechin (SPA-CE), and sucrose (SPA-SU) in 1:5 and 1:10 M ratios were used to increase their stability during storage for 77 days at 25 ± 1 °C in pH 3 buffer solution. The SPA-TA1:5 complex showed the significant highest stability of total monomeric ACN content (TMAC) with a half-life (t1/2) = 56.9 days, cyanidin-3-O-sophoroside (C3S) with t1/2 = 48.1 days and color retention (69.80 %) compare to SPA with TMAC (t1/2 = 37.4), C3S (t1/2 = 13.3) and color retention (57.2 %) after 49 days (p < 0.05). The thermal stability of SPA-TA1:5 at 60 °C improved after high-pressure processing (HPP) at 300 and 500 MPa for 10 min. Fourier-transform infrared spectroscopy (FT-IR) and molecular docking indicate copigmentation interactions, including hydrogen bonding and π-π interactions. This study demonstrates a sustainable method to stabilize non-acylated ACNs, offering a natural alternative to synthetic dyes for food and beverage applications.